The Community Knowledge, Attitude, and Practices (KAP) Regarding Household Waste Sorting and its Impact on Public Health in Denpasar, Bali - I Wayan Rediyasa; Yui Nakamura; Kaito Tanaka (Yayasan Adra Karima Hubbi, 2025)
Background. Household waste mismanagement remains a persistent environmental and public health challenge in rapidly urbanizing Indonesian cities, including Denpasar, Bali. Despite government-led campaigns promoting household waste sorting, community responses vary widely, suggesting gaps in knowledge, attitude, and practices (KAP) that may influence health outcomes. Purpose. This study investigates the level of community KAP regarding household waste sorting and evaluates its potential impact on public health indicators within urban neighborhoods of Denpasar. The objective is to identify critical behavioral determinants that strengthen or weaken waste-sorting compliance and to assess how these behavioral patterns correlate with sanitation-related health risks. Method. A cross-sectional survey was conducted involving 420 households selected through multistage cluster sampling across four districts in Denpasar. Data were collected using a validated KAP questionnaire, complemented by direct environmental observations and secondary health records from local community health centers. Results. The results indicate that although 78% of respondents show adequate knowledge about waste sorting, only 52% demonstrate positive attitudes, and merely 39% consistently practice proper waste segregation. Poor practice scores strongly correlate with higher reports of mosquito-borne illnesses and household-level sanitation hazards (p < 0.05). Regression analysis suggests that attitude mediates the translation of knowledge into practice, making it a key leverage point for behavioral change. Conclusion. This study concludes that improving public health in Denpasar requires targeted interventions that address not only informational gaps but also motivational and infrastructural barriers to waste-sorting practices. Strengthening community engagement and localized environmental health programs is essential for sustainable behavioral compliance.